Studi Analisis Hasil Batik Tulis Canting Elektrik dan Canting Manual - Soeparman Soeparman (LPPM Universitas PGRI Adi Buana Surabaya, 2013)
The purpose of this theres is to set data and qualityof the result of had made â€œbatikâ€seen from the aspeat of using manual elektric â€œcantingâ€ (a kmid of fool to drop thematerial for batik) which. Is done by batik maker.The target of this theres is using canting too as a media to make painting batik (batiktulis), qualitative research using experiment method analisis and testing to set the resulfof the batik in good quality. The strangth of color, motive, estetic and the way how toapplicate the knids of cotton cloth and â€œmoriâ€ clot by usinga set of trial lests by the sixsemester studets of art and semester VI.In this study (the ses) the population is cotton cloth and â€œmoriâ€ cloth. The way to take thesamples is by preparing two sets of clothes which consest of cotton cloth libre in size of50cm x 100cm, the number of clothes that will be used in this experiment will beprepared 10 pieces each which will be tahen over the process of coloring in the â€œcelupâ€(wash) system.Data analysis tecniq in this stuy is by analizine the resultof â€œmembatikâ€ (coloring withspecial motive) by using electric â€œcantingâ€ and done manealt seen from quality strenghtof colors, motive and estetics and then based on the proof, it is exsplaned qualitatively.From the analizing result it is hopedto be ableto bemade a use foor the general pulic andthe batik amters especialh. And also in the proces of batiklearning to mak batik of schol,we know batik is an indonesia tradisional of Indonesia and that renet can be resed as asoursce in prosess of learning.